Patient Preferences and Health State Utilities Associated with Mealtime Insulin Concentrations Among Patients with Diabetes in Italy - Matza, Louis S. (Diabetes Ther, 2019)
INTRODUCTION: Standard concentration (100 units/mL) mealtime insulin is frequently used to treat patients with type 1 (T1D) and type 2 diabetes (T2D). A more concentrated version of the medication (200 units/mL) has been available in Italy since 2016. This concentrated version is bioequivalent to the standard version and delivers the same amount of medication but in half the volume of liquid. The purpose of this study was to examine patient preferences and estimate health state utilities associated with standard and concentrated rapid-acting mealtime analog insulin. METHODS: Participants with T1D and T2D in Italy valued two health states in time trade-off interviews. The descriptions of diabetes and treatment in the two health states were identical, differing only in terms of insulin concentration (e.g., half as much liquid for the same dose, less effort needed to press the injection button, and fewer injection pens required with concentrated insulin). To ensure participants understood the health states, they were shown a short video illustrating the differences between concentrations. RESULTS: A total of 217 participants completed the interviews (49.8% male; mean age 56.1 years; 109 from Milan; 108 from Rome; 12.0% T1D; 88.0% T2D). When asked which health state they preferred, 98.2% responded the concentrated version, 0.9% said the standard version, and 0.9% had no preference. Mean [standard deviation (SD)] utilities rounded to three decimals were 0.892 (0.099) for the concentrated version and 0.884 (0.101) for the standard version. The mean (SD; p value) utility difference between the standard and concentrated rapid-acting insulin was 0.007 (0.019; p < 0.0001). CONCLUSIONS: Findings from this study provide insight into patient preferences associated with concentration of rapid-acting insulin. Although the difference in utility is small, patients consistently preferred the concentrated formulation over the standard insulin, and for some patients this difference had an impact on utility valuations. These results suggest that the concentration of rapid-acting insulin should be considered because it could affect treatment preference and quality of life. FUNDING: Eli Lilly and Company. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-019-00718-8) contains supplementary material, which is available to authorized users.